α-Glucosidase inhibitor and antioxidant activity of procyanidin, an isolated compound from Quercus gilva Blume leaves - Anastasia Wheni Indrianingsih, Amalia Indah Prihantini, Sanro Tachibana (Journal of Applied Pharmaceutical Science, 2022)
Potential candidates for antioxidants and antidiabetics from nature are needed because they are safer and have few side effects. This report performed the extraction and isolation of biologically active compounds from Quercus gilva Blume leaves. In our previous study, several active compounds, including tiliroside, catechin, and epicatechin, had been isolated from Q. gilva leaves. This study obtained the active compound from Q. gilva leaves through bioassayguided isolation by silica gel column chromatography using organic solvents from low-to-high polarity. The compound capability in scavenging free radicals was evaluated using the 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity (DPPH) assay, reducing power assay, β-carotene assay, and hydrogen peroxide (H2O2) assay. The in vitro test of the antidiabetic assay was performed against the α-glucosidase enzyme. It showed that one compound, identified as procyanidin B3, was isolated. The isolated compound has antioxidant activity IC50 of 7.86 ± 0.41 µg/ml by the DPPH test and IC50 of 34.51 ± 1.34 µg/ml by the H2O2 assay. Moreover, the α-glucosidase inhibitory activity (IC50) of the isolated compound was 40.05 ± 0.51 µg/ml. This study showed that the isolated compound from Q. gilva showed the potential for natural antidiabetic medicine and antioxidants from nature.
Keywords: Procyanidin, &alpha; -glucosidase inhibitory activity, antioxidative activity, Quercus gilva Blume.